Highly Stable Two‐Dimensional Tin(II) Iodide Hybrid Organic–Inorganic Perovskite Based on Stilbene Derivative. (5th August 2019) - Park, In‐Hyeok; Chu, Leiqiang; Leng, Kai; Choy, Yu Fong; Liu, Wei; Abdelwahab, Ibrahim; Zhu, Ziyu; Ma, Zhirui; Chen, Wei; Xu, Qing‐Hua; Eda, Goki; Loh, Kian Ping
Abstract: Hybrid organic–inorganic perovskites have recently emerged as potential disruptive photovoltaic technology. However, the toxicity of lead used in state‐of‐the‐art hybrid perovskites solar cell prevents large‐scale commercialization, which calls for lead‐free alternatives. Sn‐based perovskites have been considered as alternatives but they are limited by rapid oxidation and decomposition in ambient air. Here, an Sn‐based two‐dimensional hybrid organic–inorganic perovskites [A2 B( n ‐1) Sn n I(3 n +1) ] ( n = 1 and 2) are reported with improved air stability, using bulky stilbene derivatives as the organic cations (2‐(4‐(3‐fluoro)stilbenyl)ethanammonium iodide (FSAI)). The moisture stability of the [(FSA)2 SnI4 ] perovskites is attributed to the hydrophobic properties of fluorine‐functionalized organic chains (FSA), as well as the strong cohesive bonding in the organic chains provided by H bonds, CH···X type H bonds, weak interlayer F···F interaction, and weak face‐to‐face type π‐π interactions. The photodetector device fabricated on exfoliated single crystal flake of [(FSA)2 SnI4 ] exhibits fast and stable photoconductor response. Abstract : The use of large organic cations made of stilbene derivatives is reported to generate new variants of air stable Sn‐based two‐dimensional hybrid organic–inorganic perovskites (HOIPs), [(FSA)2 (MA)( n –1) Sn n I(3 n +1) ] ( n = 1 and 2; (2‐(4‐(3‐fluoro)stilbenyl)ethanammonium iodide = FSAI and methylammonium iodide = MAI). The single crystal of Sn‐HOIP shows excellent air stability and can be fabricated into field effect transistors and fast photodetectors.